2014
DOI: 10.5152/jtgga.2014.14170
|View full text |Cite
|
Sign up to set email alerts
|

The effects of subchorionic hematoma on pregnancy outcome in patients with threatened abortion

Abstract: Objective:To assess the effects of ultrasonographically detected subchorionic hematomas on pregnancy outcomes in patients with vaginal bleeding within the first half of pregnancy. Material and Methods:Patients diagnosed with threatened abortion due to painless vaginal bleeding and who were followed up in an inpatient service during the first vaginal bleeding between January 2009 and December 2010 were included in this retrospective cohort study. Patients were divided into two groups according to the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 24 publications
3
19
0
Order By: Relevance
“…Intrauterine blood pooling was identified in three women in the spontaneous abortion group by ultrasonography. The difference between the groups was significant, in agreement with the findings of Sukur et al, 21 who reported an increased risk of spontaneous abortion in women with an ultrasonographically detected subchorionic hematoma in the first 20 weeks of pregnancy. However, it does not influence late pregnancy outcomes.…”
Section: Variablesupporting
confidence: 91%
See 1 more Smart Citation
“…Intrauterine blood pooling was identified in three women in the spontaneous abortion group by ultrasonography. The difference between the groups was significant, in agreement with the findings of Sukur et al, 21 who reported an increased risk of spontaneous abortion in women with an ultrasonographically detected subchorionic hematoma in the first 20 weeks of pregnancy. However, it does not influence late pregnancy outcomes.…”
Section: Variablesupporting
confidence: 91%
“…The difference between the groups was significant, in agreement with the findings of Sukur et al,21 who reported an increased risk of spontaneous abortion in women with an ultrasonographically detected subchorionic hematoma in the first 20 weeks of pregnancy. The difference between the groups was significant, in agreement with the findings of Sukur et al,21 who reported an increased risk of spontaneous abortion in women with an ultrasonographically detected subchorionic hematoma in the first 20 weeks of pregnancy.…”
supporting
confidence: 91%
“…Sub-chorionic hematoma is a sonographically detected anechoic area with a falciform shape that increases the risk of spontaneous abortion [131]. Placental dysfunction, insufficient angiogenesis, and chronic inflammation are underlying causes of early pregnancy bleeding, and these factors can even result in preterm labor or perinatal mortality [132]. Progesterone has a significant role both in maturation of fetus and cytokine balance.…”
Section: α-Lipoic Acid In Clinical Trialsmentioning
confidence: 99%
“…A study reported that the presence of SCH in patients who underwent IVF-ET/FET had no influence on the incidence of spontaneous miscarriage or live birth rate (15). As for natural pregnancies, however, most studies have suggested a significant correlation between SCH and adverse obstetric outcomes (2,33). Moreover, the occurrence of SCH could increase the risk of spontaneous miscarriage, premature delivery, placental abruption, and gestational hypertension (34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…If the hematoma is large and clots have formed, petechial or linear hyperechoic areas can be detected around the gestational sac and under the chorionic membrane, whose lower edges are mostly connected to the inner cervical canal. The existence of SCH is possibly related to the occurrence of adverse obstetric outcomes, such as miscarriage (2). However, the induction of SCH remains unclear, and the occurrence of SCH is reportedly related to thrombosis (3).…”
Section: Introductionmentioning
confidence: 99%